2014
DOI: 10.1002/mus.24136
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐derived precursor schwann cell myelination capacity in focal tibial demyelination

Abstract: SKP-SCs are robustly capable of myelination. They improve the recovery of a focal tibial nerve demyelination model by myelinating a measured percentage of axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…These diverse multipotent MSCs can also be differentiated into cells of the ectodermal lineage including neurons and glial cells. Various studies using skin-derived MSCs, adipose tissue-derived MSCs (AMSCs), bone marrow-derived MSCs, and umbilical cord-derived MSCs have been performed in attempts to differentiate them into SCs under diverse conditions [9,10,11,12]. Although bone marrow-derived MSCs are one of the most intensively studied types of MSC associated with SC differentiation, they are limited in terms of clinical applications because of their low yields and the need for invasive procedures to isolate them [13].…”
Section: Introductionmentioning
confidence: 99%
“…These diverse multipotent MSCs can also be differentiated into cells of the ectodermal lineage including neurons and glial cells. Various studies using skin-derived MSCs, adipose tissue-derived MSCs (AMSCs), bone marrow-derived MSCs, and umbilical cord-derived MSCs have been performed in attempts to differentiate them into SCs under diverse conditions [9,10,11,12]. Although bone marrow-derived MSCs are one of the most intensively studied types of MSC associated with SC differentiation, they are limited in terms of clinical applications because of their low yields and the need for invasive procedures to isolate them [13].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known regarding the role of SKPs in wound healing, but several studies have shown that SKP‐derived Schwann cells may help in promoting peripheral nerve regeneration . SKP‐derived Schwann cells or SKPs themselves are, in a model of nerve injury, capable of inducing remyelination and regeneration of peripheral nerves . Indeed, without predifferentiation, grafted proliferative SKPs induce positive effects on cutaneous nerve regeneration.…”
Section: Therapeutic Strategies To Improve Wound Healing and Reinnervmentioning
confidence: 98%
“…We have previously injected lentiviral enhanced blue fluorescent protein (BFP) SCs into Thy‐1 green fluorescent protein (GFP) rats that underwent doxorubicin‐induced focal myelination . Our group showed that these cells may aid regeneration through growth factor production, debris clearance, and myelination (Figure ).…”
Section: Skin‐derived Precursor Cellsmentioning
confidence: 99%